Coping mechanisms for students with mental disorders: An exploratory qualitative study at Busitema University's Mbale and Busia Campuses. - Enid Kawala Kagoya; Joseph Mpagi; Paul Waako; Martha R L Muhwezi; Agnes Namaganda; Allan G Nsubuga; Christine Etoko Atala; Francis Okello; Ambrose Okibure; Ronald Kibuuka; Ernest Wandera; Kalisiti Ndamanywa; et al. (PLOS Global Public Health)
In recent years, Ugandan universities have faced a rising incidence of mental health issues among students, with prevalence rates of mental disorders reaching up to 60% among undergraduates. These challenges significantly impact both academic performance and social interactions. This study aimed to investigate the coping mechanisms among students with mental disorders at Busitema University. We conducted 42 key informant interviews with students diagnosed with mental disorders, as determined by the Mini International Neuropsychiatric Interview. Interviews were guided by a structured protocol developed by the research team, and all participants provided informed consent. The interviews were audiotaped, transcribed verbatim, and analyzed using thematic analysis. This approach was chosen for its efficiency and directness. Nvivo software facilitated the coding and organization of themes. The study identified several coping strategies used by students at the two Busitema University campuses. Five main themes emerged: Alcohol and Substance Use, Use of Sedatives, Social and Personal Initiatives, Seeking Counseling Services, Withdrawal and Confrontation, and Faith Healing. Various subthemes were also noted, including substance use, withdrawal, confrontations, witchcraft, participation in co-curricular activities, abortions, and seeking psychosocial support. These findings are detailed in Table 2. Addressing the mental health challenges faced by university students requires a thorough understanding of their coping strategies. While some strategies are self-developed, others involve university-led interventions. It is crucial to reinforce effective coping mechanisms and address detrimental ones to improve students' mental health outcomes. Mental disorders, coping strategies, university students, Uganda.